Comprehensive analysis of PTEN status in breast carcinomas. Issue 2 (12th February 2013) - Jones, Natalie; Bonnet, Françoise; Sfar, Sana; Lafitte, Marie; Lafon, Delfine; Sierankowski, Ghislaine; Brouste, Véronique; Banneau, Guillaume; Tunon de Lara, Christine; Debled, Marc; MacGrogan, Gaëtan; Longy, Michel; et al.
<x xml:space="preserve">Abstract</x> PTEN plays a well‐established role in the negative regulation of the PI3K pathway, which is frequently activated in several cancer types, including breast cancer. A nuclear function in the maintenance of chromosomal stability has been proposed for PTEN but is yet to be clearly defined. In order to improve understanding of the role of PTEN in mammary tumorigenesis in terms of a possible gene dosage effect, its PI3K pathway function and its association with p53, we undertook comprehensive analysis of PTEN status in 135 sporadic invasive ductal carcinomas. Four PTEN status groups were defined; complete loss (19/135, 14%), reduced copy number (19/135, 14%), normal (86/135, 64%) and complex (11/135, 8%). Whereas the PTEN complete loss status was significantly associated with estrogen receptor (ER) negativity (p=0.006) and in particular the basal‐like phenotype (p<0.0001), a reduced PTEN copy number was not associated with hormone receptor status or a particular breast cancer subtype. Overall, PI3K pathway alteration was suggested to be involved in 59% (79/134) of tumors as assessed by human epidermal growth factor receptor 2 overexpression, PIK3CA mutation or a complete loss of PTEN. A complex PTEN status was identified in a tumor subgroup which displayed a specific, complex DNA profile at the PTEN locus with a strikingly similar highly rearranged pan‐genomic profile. All of these tumors had relapsed and were associated with a poorer prognosis in the context of node negative disease (p=1.4 × 10−13) thus may represent a tumor subgroup with a common molecular alteration which could be targeted to improve clinical outcome.